2011
DOI: 10.1007/s12020-011-9517-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thyroid function and blood pressure in school-aged subjects without overt thyroid disease

Abstract: This study was performed to ascertain whether a relationship exists between thyroid function and blood pressure in school-aged Chinese subjects without overt thyroid disease. A cross-sectional survey of 880 subjects (541 females and 339 males) aged 7-18 years in Bengbu, Anhui province was conducted. The investigation, which was based on a stratified random cluster sampling method, included a questionnaire and measurements of blood pressure, height, and body weight. Fasting blood samples were taken for measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
3
22
0
2
Order By: Relevance
“…Moreover, many studies have correlated subclinical hypothyroidism with atherosclerosis, endothelial dysfunction, and coronary heart disease [2, 3]. Recently, it has been shown that thyroid stimulating hormone (TSH) levels even within the normal range are positively associated with systolic and diastolic blood pressure [4, 5]. This may suggest a direct action of TSH on the cardiovascular system especially as extrathyroidal actions of TSH have been reported [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many studies have correlated subclinical hypothyroidism with atherosclerosis, endothelial dysfunction, and coronary heart disease [2, 3]. Recently, it has been shown that thyroid stimulating hormone (TSH) levels even within the normal range are positively associated with systolic and diastolic blood pressure [4, 5]. This may suggest a direct action of TSH on the cardiovascular system especially as extrathyroidal actions of TSH have been reported [6].…”
Section: Introductionmentioning
confidence: 99%
“…High‐normal TSH levels have been associated with higher weight, BMI and alterations in body fat distribution . A positive association of TSH levels and blood pressure has also been reported . Higher levels of serum FT4 in euthyroid individuals have been associated with lower BMI and abdominal subcutaneous fat mass area .…”
Section: Discussionmentioning
confidence: 95%
“…32,33 A positive association of TSH levels and blood pressure has also been reported. 34,35 Higher levels of serum FT4 in euthyroid individuals have been À0Á11 (À0Á20, À0Á02)* À0Á07 (À0Á15, 0Á02) Reference À0Á08 (À0Á17, 0Á01) À0Á09 (À0Á17, 0) 0 (À0Á03, 0Á02)…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%
“…Cerbone et al described no relationship between TSH levels and IQ or behaviour in children with SCH. (124) Verbal fluency and encoding test scores were also not affected by SCH in another case-control study by Ergür et al (126) Pubertal delay was not found to be associated with SCH by Cerbone et al and Rapa et al (124,127) Cardiovascular risk factors SCH was associated with hypertension in children and adolescents in two cross-sectional studies by Chen et al and Ittermann et al (128,129) Furthermore, triglyceride levels, homocysteine levels and waist-to-hip ratios were higher in children with SCH compared to controls in another crosssectional study by Cerbone et al, which also found that highdensity lipoprotein cholesterol was lower in SCH patients. (130) …”
Section: Skeletal Developmentmentioning
confidence: 95%